Horizontal transfer of mitochondria between mammalian cells: beyond co-culture approaches - Berridge, Michael V; McConnell, Melanie J; Grasso, Carole; Bajzikova, Martina; Kovarova, Jaromira; Neuzil, Jiri (Current opinion in genetics & development, 2016)
Current dogma holds that genes are the property of individual mammalian cells and partition between daughter cells during cell division. However, and rather unexpectedly, recent research has demonstrated horizontal cell-to-cell transfer of mitochondria and mitochondrial DNA in several mammalian cell culture systems. Furthermore, unequivocal evidence that mitochondrial DNA transfer occurs in vivo has now been published. While these studies show horizontal transfer of mitochondrial DNA in pathological settings, it is also possible that intercellular mitochondrial transfer is a fundamental physiological process with a role in development and tissue homeostasis.
Keywords: Gene Transfer, Horizontal; buněčné dělení; Animals; mitochondrie; Cell Communication; přenos genů horizontální; mezibuněčná komunikace; lidé; zvířata; Cell Division; Mitochondria; DNA, Mitochondrial; mitochondriální DNA; Humans